2020
DOI: 10.3389/fimmu.2020.01913
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lymphocyte Subsets for Early Identification of Non-Remission to TNF Inhibitors in Rheumatoid Arthritis

Abstract: Background: TNF inhibitors (TNFis) are widely used for the treatment of rheumatoid arthritis (RA), although the response rates to this therapy in patients with RA remains heterogeneous and < 50% achieve remission (REM). Objective: To analyze baseline peripheral blood leukocytes profiles in order to search for biomarkers identifying patients who will most likely not achieve REM under TNFi treatment. Methods: A prospective bi-center pilot study including 98 RA patients treated with TNFis and followed-up during 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Leandro has deepened this controversy by suggesting that this variability could be due to the absence of a pattern in the B-cell compartment population in patients with RA [ 24 ]. Previous results from our research group and from other researchers have supported the hypothesis of the importance of B-cell dynamics in response to biological therapy [ 25 , 26 , 27 ]. Moreover, research from our group identified the role of BAFF in the development of immunogenicity and, therefore, in B-cell activation and its involvement in the response to TNFis [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Leandro has deepened this controversy by suggesting that this variability could be due to the absence of a pattern in the B-cell compartment population in patients with RA [ 24 ]. Previous results from our research group and from other researchers have supported the hypothesis of the importance of B-cell dynamics in response to biological therapy [ 25 , 26 , 27 ]. Moreover, research from our group identified the role of BAFF in the development of immunogenicity and, therefore, in B-cell activation and its involvement in the response to TNFis [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…With these findings, it could be hypothesised that in seropositive patients who are good responders, their disease is mediated by the chosen mechanism of action and could demonstrate less BAFF production by inflammatory cells and greater uptake by the specific receptor expressed on B cells [ 23 ]. This hypothesis has been reinforced by previous studies in which the proportion of B lymphocytes at baseline and 6 months after treatment with TNFis is different depending on the response to treatment [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 79%
“…Different PBMC subsets were analyzed at baseline and after 6 months of TNFi treatment, in order to identify whether PBMC profile changes after TNFi therapy ( , 6-0 months). A previous analysis in our cohort of patients showed that a higher percentage of baseline B cells (especially naive B cells) was associated with attaining REM after 6 months of TNFi treatment (13).…”
Section: Pbmc Subset Changes After 6 Months Of Tnfi Treatmentmentioning
confidence: 50%
“…In a previous study conducted by our group including the same cohort of patients, the correction of multiple comparisons using the Benjamini-Hochberg (BH) method with a predefined value FDR = 0.25 was applied (free software used MEV 2.0). This analysis demonstrated that the associations of either total or naive B lymphocytes with REM were not due to chance (13). Therefore, clinical follow-up analyses after initiation of TNFi therapy have been performed in these two subpopulations.…”
Section: Statistical Analysesmentioning
confidence: 85%
See 1 more Smart Citation